KEWENANGAN KONSTITUSIONAL PRESIDEN TERHADAP “HAL IHWAL KEGENTINGAN YANG MEMAKSA” - Siti Marwiyah (Masalah-Masalah Hukum, 2015)
The Constitutional of the Republic of Indonesia (UUD NRI 1945) gives nit a little authorizes to the President. One of the authority is to set “happenings crunch yhat fonced” because the country is not always in a state of normal//peace/stable. At the time of the reverse of President as head of state was given the constitutional authorithy to establish a state of emergency in the form of Government Regulation in Leu of Law (PERPPU)